Challenging the “old boys club” in academia: Gender and geographic representation in editorial boards of journals publishing in environmental sciences and public health - Dada, Sara; van Daalen, Kim Robin; Barrios-Ruiz, Alanna; Wu, Kai-Ti; Desjardins, Aidan; Bryce-Alberti, Mayte; Castro-Varela, Alejandra; Khorsand, Parnian; Santamarta Zamorano, Ander; Jung, Laura; Malolos, Grace; Li, Jiaqi; et al. (PLOS Global Public Health, 2022)
In light of global environmental crises and the need for sustainable development, the fields of public health and environmental sciences have become increasingly interrelated. Both fields require interdisciplinary thinking and global solutions, which is largely directed by scientific progress documented in peer-reviewed journals. Journal editors play a critical role in coordinating and shaping what is accepted as scientific knowledge. Previous research has demonstrated a lack of diversity in the gender and geographic representation of editors across scientific disciplines. This study aimed to explore the diversity of journal editorial boards publishing in environmental science and public health. The Clarivate Journal Citation Reports database was used to identify journals classified as Public, Environmental, and Occupational (PEO) Health, Environmental Studies, or Environmental Sciences. Current EB members were identified from each journal’s publicly available website between 1 March and 31 May 2021. Individuals’ names, editorial board roles, institutional affiliations, geographic locations (city, country), and inferred gender were collected. Binomial 95% confidence intervals were calculated for the proportions of interest. Pearson correlations with false discovery rate adjustment were used to assess the correlation between journal-based indicators and editorial board characteristics. Linear regression and logistic regression models were fitted to further assess the relationship between gender presence, low- and middle-income country (LMIC) presence and several journal and editor-based indicators. After identifying 628 unique journals and excluding discontinued or unavailable journals, 615 journal editorial boards were included. In-depth analysis was conducted on 591 journals with complete gender and geographic data for their 27,772 editors. Overall, the majority of editors were men (65.9%), followed by women (32.9%) and non-binary/other gender minorities (0.05%). 75.5% journal editorial boards (n = 446) were composed of a majority of men (>55% men), whilst only 13.2% (n = 78) demonstrated gender parity (between 45–55% women/gender minorities). Journals categorized as PEO Health had the most gender diversity. Furthermore, 84% of editors (n = 23,280) were based in high-income countries and only 2.5% of journals (n = 15) demonstrated economic parity in their editorial boards (between 45–55% editors from LMICs). Geographically, the majority of editors’ institutions were based in the United Nations (UN) Western Europe and Other region (76.9%), with 35.2% of editors (n = 9,761) coming solely from the United States and 8.6% (n = 2,373) solely from the United Kingdom. None of the editors-in-chief and only 27 editors in total were women based in low-income countries. Through the examination of journal editorial boards, this study exposes the glaring lack of diversity in editorial boards in environmental science and public health, explores the power dynamics affecting the creation and dissemination of knowledge, and proposes concrete actions to remedy these structural inequities in order to inform more equitable, just and impactful knowledge creation.
Keywords: 2000 à aujourd'hui; 2020-2029; approches et analyses; discipline; discours dominant; intersectionnalité; médecine; projet charge mentale; périodes historiques; racisme; santé; santé publique; sciences; sexisme; systèmes d'oppressions; thématiques

Défaire le discours sexiste dans les médias - Lamy, Rose (Éditions Points, 2022)
Qu’est-ce qu’elle faisait dehors à cette heure ? Avait-elle bu ? Que portait-elle ? Il ne peut pas l’avoir violée, je m’en porte garant, c’est mon ami. C’était une autre époque. Il faut séparer l’homme de l’artiste. C’est un drame, un crime passionnel, le geste fou d’un amoureux éconduit. Pourquoi n’a-t-elle pas porté plainte avant ? C’était un dérapage, une maladresse, un geste déplacé. Il ne pensait pas à mal, c’est quelqu’un de bien. On ne peut plus rien dire. Les féministes sont des folles hystériques. « Depuis trois ans, je collecte et décortique des centaines d’exemples d’un discours sexiste dans la presse, à la télévision ou à la radio. Ce sexisme ne dit jamais son nom, mais c’est bien lui qui conduit les rédactions à taire ou à reléguer les violences sexuelles en périphérie des journaux. Lui qui se loge dans le choix d’un mot ou d’une virgule, participant à la culpabilisation des victimes et à la déresponsabilisation des accusés. Comment lutter contre le sexisme quand il est perpétué et amplifié par les médias ? Il est temps d’explorer les fondements de ce discours, pour en défaire les mécanismes et nous en libérer. »
Section: 289 pages ; 18 cm
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; 2020-2029; approches et analyses; arts; com5170; communication; cours; discipline; discours dominant; discours médiatique; essai; europe; france; journalisme; militance; patriarcat; premier cycle; périodes historiques; régions géographiques; sexisme; sofia; systèmes d'oppressions; thématiques; violences; études littéraires

Les rappeuses québécoises sur le devant de la scène : autorité lyrique de la voix féminine chez Donzelle et MCM - Simard, Mathieu; Kirouac Massicotte, Isabelle (Analyses, 2022)
Si le rap accède de nos jours à une certaine légitimité culturelle, le travail des rappeuses reste encore largement dans l’ombre. Ce sont les voix masculines qui se sont imposées dans le milieu du rap québécois, comme en témoigne l’intérêt que leur manifestent les maisons de disques (labels) et les stations de radio commerciales. Cet article propose une analyse des textes de deux rappeuses, MCM et Donzelle, afin d’observer comment elles construisent leur autorité lyrique, c’est-à-dire la crédibilité de leur prise de parole, la validité idéologique de leurs propos et la valeur esthétique de leur chant. Trois stratégies sont mises en place. Les rappeuses intègrent d’abord à leur rap un point de vue sexiste afin de reproduire le contexte social et discursif dans lequel elles oeuvrent. Ensuite, elles proposent une autre représentation des femmes afin de répondre à l’imaginaire sexiste dont s’est parfois nourrie la parole rap. Enfin, MCM et Donzelle créent leur propre esthétique, jouant pour ce faire avec les codes du trash, prégnant dans leur art
https://id.erudit.org/iderudit/1090843ar
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; amériques; approches et analyses; arts; discipline; discours dominant; périodes historiques; québec; ressource en ligne; régions géographiques; sexisme; systèmes d'oppressions; thématiques; travail; violences; études littéraires

Justice and the politics of difference - Young, Iris Marion; Allen, Danielle S. (Princeton University Press, 2022)
"In this classic work of feminist political thought, Iris Marion Young challenges the prevailing reduction of social justice to distributive justice. The starting point for her critique is the experience and concerns of the new social movements that were created by marginal and excluded groups, including women, African Americans, and American Indians, as well as gays and lesbians. Young argues that by assuming a homogeneous public, democratic theorists fail to consider institutional arrangements for including people not culturally identified with white European male norms. Consequently, theorists do not adequately address the problems of an inclusive participatory framework. Basing her vision of the good society on the culturally plural networks of contemporary urban life, Young makes the case that normative theory and public policy should undermine group-based oppression by affirming rather than suppressing social group differences"
Section: x, 286 pages ; 24 cm.
Keywords: 2000 à aujourd'hui; 2010-2019; amérique du nord; amériques; approches et analyses; cours; cycles supérieurs; discipline; discours dominant; fem9000; inégalités; justice sociale; phi4336; philosophie; premier cycle; périodes historiques; queer; régions géographiques; sciences humaines; systèmes d'oppressions; thématiques; états-unis

Que fait #MeToo à la littérature ? - Zenetti, Marie-Jeanne (Revue critique de fixxion française contemporaine, 2022)
Que fait #MeToo fait à la lecture, à la critique et à l’enseignement des textes littéraires ? Le mouvement #MeToo a contribué à une large prise de conscience quant aux enjeux linguistiques liés aux violences sexuelles et sexistes : lutter contre de ces violences suppose d’abord de nommer un viol un viol. Mais une telle exigence de désambiguïsation peut entrer en contradiction avec la complexité interprétative valorisée dans le cadre de la lecture littéraire. Elle présenterait par ailleurs le risque d'inviter à lire des textes éloignés de nous dans le temps et l’espace en les évaluant à l’aune de notions et d’une morale contemporaines jugées anachroniques. Prolongeant les réflexions récentes de Gisèle Sapiro (Peut-on dissocier l’œuvre de l’auteur ?) et d’Hélène Merlin-Kajman (La littérature à l’ère de MeToo), cet article étudie la réception du récit de Vanessa Springora, Le consentement (2020). En interrogeant la polarisation des discours critiques et théoriques entre une lecture “féministe” et une lecture “littéraire” parfois présentées comme incompatibles, il pose la question du lien possible entre violences sexuelles et pratiques interprétatives. Il théorise une pratique de lecture soucieuse de contextualiser l’usage des modèles interprétatifs mobilisés dans l’analyse littéraire et de les critiquer en interrogeant les rapports de pouvoir qu’ils dissimulent. Il défend ainsi l’hypothèse que le mouvement #MeToo invite les littéraires à réévaluer leurs pratiques et leurs paradigmes de lecture en fonction de ce qu’ils rendent possible.
Keywords: 2000 à aujourd'hui; 2020-2029; approches et analyses; arts; discipline; discours dominant; europe; france; metoo; patriarcat; périodes historiques; ressource en ligne; régions géographiques; systèmes d'oppressions; thématiques; violences; violences sexistes et sexuelles; études littéraires